Assessing judicial efficiency of Egyptian First Instance Courts: A DEA analysis - Nora Elbialy; Miguel A. García-Rubio (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
Egypt started a recent judicial reform program in 2007, which can be considered the first ever since the establishment of the National Egyptian Judicial System in 1952. It focuses mainly on solving organizational problems within First Instance Courts (FIC), as they form the active cell of the Egyptian judicial system. However the efficiency of FICs is still doubtable to a large extent. This paper provides for the first time an efficiency analysis of 22 FICs in Egypt using the technique of Data Envelop Analysis (DEA). The main strength of this study is to consider the number of computers per court, as none of the previous papers on court efficiency has included a capital variable when defining their court production function before. Our results show that there are no significant differences observed in terms of management efficiency between the civil and criminal FICs, however criminal FICs districts are superior with respect to their corresponding civil districts in terms of program efficiency.
Keywords: 330; egyptian judicial system; efficiency; data envelopment analysis; Justiz; Technische Effizienz; Data-Envelopment-Analyse; Ägypten